The easiest way is to use the quadratic formula, you're right!
The solutions of a quadratic equation
ax² + bx + c = 0
are
x = [ - b ± √(b² - 4ac)] / 2a
For 6x² + 17x - 39 = 0,
a = 6, b = 17 and c = -39, so
x = [ - 17 ± √(17² - 4·6·(-39))] / 2·6
x = [ - 17 ± √(289 + 936)] / 12
x = [ - 17 ± √1225] / 12
x = [- 17 ± 35] / 12
So the two solutions are
=> x = [- 17 + 35] / 12 = 18/12 = 3/2
and
=> x = [- 17 - 35] / 12 = -52/12 = -13/3
__________
If you didn't use the quadratic formula, you could also factor
6x² + 17x - 39 = 0
(2x - 3)(3x + 13) = 0
=> x = 3/2, x = -13/3
___________
Hope this helps.
2007-05-24 09:47:37
·
answer #1
·
answered by M 6
·
7⤊
0⤋
A quick check is the discriminant b^2-4ac
= 289 +24*39 which comes to 1225 which is 35^2 so it will factorise easily
x = -b+-sqr(discriminant)/2a
x = (-17 +-35)/12
x = 1 1/2 or x = -4 1/3
( 2x-3)( 3x+13)
2007-05-24 18:07:42
·
answer #2
·
answered by welcome news 6
·
0⤊
1⤋
you may use this formula of quadratic equation for finding the unknown values in this case.
given eq. : 6x² + 17x - 39 = 0
quadratic eq.:
ax² + bx + c = 0
x = [ - b ± â(b² - 4ac)] / 2a
there are two answers to this equation, because
there is ± with respect to the root of the equations.
one answer is:
x = 1.5
the other is:
x = - 4.3333333
ok.
2007-05-24 17:04:59
·
answer #3
·
answered by edison c d 4
·
0⤊
0⤋
The quadratic equation formula will work. If you have a negative c coefficient and a value of a not equal to 1 that is usually a good sign of it needing the quadratic formula.
2007-05-24 16:49:12
·
answer #4
·
answered by Anonymous
·
0⤊
2⤋
6x^2+17x -39 = 0
6^2 -9x +26x -39 =0
3x(2x - 3) +13(2x - 3) =0
(2x - 3)(3x + 13) =0
2x -3 =0 or 3x +13 =0
2x = 3 or 3x = -13
x =3/2 or x = -13/3
2007-05-25 07:03:38
·
answer #5
·
answered by billako 6
·
0⤊
1⤋
6x² + 17x - 39 = 0
x = [-17 +- SQRT(17² - 4(6)(-39)] / (2)(6)
x = [-17 +- 35] / 12
x = 1 1/2, -4 1/3
2007-05-24 19:07:43
·
answer #6
·
answered by Kemmy 6
·
0⤊
1⤋
6x²+17x-39=0
(2x-3)(3x+13)=0
therefore x=3/2 or -13/3
Hope that helps
2007-05-25 05:47:26
·
answer #7
·
answered by Charlene 2
·
1⤊
0⤋
6x² + 17x - 39 = 0
Solving with the quadractic equation
x = (-b +- â(b² - 4ac))/2a
x = (-17 +- â(289 + 936))/12
x = (-17 +- â(1225))/12
x = (-17 +- 35)/12
x = -0.433, x = 1.5
.
2007-05-24 16:52:59
·
answer #8
·
answered by Robert L 7
·
0⤊
0⤋
It factors to
(2x - 3)(3x + 13) = 0
================
quadratic formula is
(1 / 2a)(-b +- sqrt (b^2 - 4ac))
in your case...
a = 6
b = 17
c = -39
Starting from the inside...
b^2 - 4ac
= (17)^2 - 4(6)(-39)
= 289 + 936
= 1225
square root of that is...
sqrt 1225 = 35
So, now you have
- b +- 35
= -17 +- 35
= 18 and -52
AND
(1 / 2a) = 1 / 2*6 = 1/12
So....
(1/12)(18) AND (1/12)(-52)
or...
18/12 AND -52/12
simplified...
3/2 AND -13/3
2007-05-24 16:51:52
·
answer #9
·
answered by Mathematica 7
·
0⤊
4⤋
6x2 + 17x - 39 = 0
6x2 + 26x - 9x - 39 = 0
2x(3x + 13) - 3( 3x + 13) = 0
therefore, (2x - 3) * (3x + 13) = 0
therfore, 2x -3 = 0 OR 3x + 13 =0
therefore, x = 3/2 OR x = -13/3
2007-05-24 16:51:23
·
answer #10
·
answered by deepak s 1
·
0⤊
2⤋